2013
DOI: 10.1155/2013/856750
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of microRNA-155 in Various Carcinomas: Results from a Meta-Analysis

Abstract: Abstract. BACKGROUND:Recent studies have shown that microRNAs (miRNA) have prognostic values in cancers. This meta-analysis seeks to summarize the global predicting role of miR-155 for survival in patients with a variety of carcinomas. METHODS: Eligible studies were identified through multiple search strategies. Data were extracted from studies investigating the relationship between miR-155 expression and survival in cancer patients. Combined hazard ratios (HRs) of miR-155 for outcome were analyzed. RESULTS: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…In contrast with some of the literature (17, 18, 33-37), we found that in most of the analyzed cancer datasets, miR-155 expression and TP53 mRNA expression by itself were not sufficient to be associated with OS ( Table 1 ). In fact, significant correlations between miR-155 and survival could only be found in the leukemia cohorts.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with some of the literature (17, 18, 33-37), we found that in most of the analyzed cancer datasets, miR-155 expression and TP53 mRNA expression by itself were not sufficient to be associated with OS ( Table 1 ). In fact, significant correlations between miR-155 and survival could only be found in the leukemia cohorts.…”
Section: Discussioncontrasting
confidence: 99%
“…In the 17p deletion group, miR-155 was the most upregulated miRNA (14). Moreover, we and others have demonstrated that miR-155 has prognostic significance in multiple types of tumors, including leukemia (15, 16) and lung cancer (17, 18). …”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Relevant works are listed in Tab. 1, including selected adopted information from meta-analysis of He and coworkers [96]. These authors summarize eligible studies and show that higher expression of miR-155 is associated with poor survival in patients with diverse types of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a significant increase in the expression of miR-155 was observed in fibroblast cells and tissues from rheumatoid arthritis patients [24]. MiR-155 is a typical multifunctional miRNA that plays crucial role in various physiological and pathological processes, such as hematopoietic lineage differentiation, immunity, cancer, cardiovascular disease, and inflammatory response [25, 26]. …”
Section: Introductionmentioning
confidence: 99%